The degree sequences of a graph with restrictions - Rikio Ichishima; Francesc A. Muntaner-Batle; Miquel Rius-Font; Yukio Takahashi (Indonesian Journal of Combinatorics, 2021)
Two finite sequences s1 and s2 of nonnegative integers are called bigraphical if there exists a bipartite graph G with partite sets V1 and V2 such that s1 and s2 are the degrees in G of the vertices in V1 and V2, respectively. In this paper, we introduce the concept of 1-graphical sequences and present a necessary and sufficient condition for a sequence to be 1-graphical in terms of bigraphical sequences.